Exploring the interplay between microplastics, polyciclic aromatic hidrocarbons and biofilms in freshwater - José, Sílvia (2022)
Water pollution resulting from domestic and industrial use of non-biodegradable materials such as plastics is a major concern. Most plastics are only fragmentable giving rise to small fragments that will persist within the environment and interact with all elements that make up the ecosystem. To date, research has focused largely on the pollution of the oceans with plastics, but the impact of this of pollution on freshwater bodies and soils is as large or as relevant.In the present work, we investigated the ability of five different plastics to adsorb PAHs and functioning as a surface for biofilm assembly with the ultimate goal of evaluating the impact on human health. The ability of polyethylene terephthalate (PET), high desinty polyethylene (HDPE), low density polyethylene (LDPE), polypropylene (PP) and polystyrene (PS) to adsorb benzo-(a)-pyrene (BaP), a group 1 carcinogenic compound, and pyrene (Pyr) a less toxic compound that we detected in different water samples in a previous study was evaluated by HPLC-MS. All the plastics were able to adsorb BaP and Pyr from the water. The extent of this retention was ruled out by the period of contact, plastic and PAH characteristics. In paralel, the ability of bacterial species isolated from freshwater responsible for infections in humans (E.coli, K. pneumoniae and Aeromonas sobria) to assemble biofilms on plastics was evaluated by scanning electron microscopy (SEM) and viable colony forming units (CFU) were evaluated by platting on selective media after 1 and 3 months. More than 300 per mL were recovered after 1 and 3 months. Bacteria assembled biofilms on different plastics showing special tropism to LDPE as shown in figure 1. The present results show that plastics can adsorb PAH present in water and function as surfaces for biofilm assembly by different human pathogens. The impact of PAH adsorbed in plastics on bacterial biofilm assembly is a work on progress, as well as, the toxicity effects on human cells.